Model Dakwah Compliance Gaining oleh Kyai Pesantren (Compliance Gaining Dakwah Model by the Kyai of Islamic Boarding School) - Mochammad Irfan Achfandhy (Jurnal Dakwah Risalah, 2020)
Kyai Fachruddin Dasuki as a boarding school caretaker tries to increase the religiosity of the community by a sermon. The great enthusiasm of the community is the result of the construction of the messages by da'wah. The purpose of this research is to examine the construction of persuasion da'wah messages and efforts to form an attitude of public compliance. This study used a qualitative approach that was descriptive and the research strategy used a narrative by retelling the da'wah activities with a descriptive narrative chronology. The findings of Kyai Fachruddin Dasuki's research on da'wah are not only persuasive but more oriented towards the goal of gaining compliance, the community becomes obedient and follows the contents of the da'wah message voluntarily without coercion. The material presented consists of five elements including; reward, punishment, expertise, personal commitment and impersonal commitment. The entire message of this da'wah is conveyed by public communication guided by the book Nashoikhul Ibad by Imam an-Nawawi.